Akulturasi arsitektur lokal dan modern pada bangunan P-House, Salatiga - Adityo Purnomo; Bachtiar Fauzy (ARTEKS : Jurnal Teknik Arsitektur, 2020)
Local and modern acculturation architecture in P-House building, Salatiga Local and modern acculturated house concept is widely applied, one of which is the P-House by Budi Pradono in Salatiga. Understanding about of the existence of local and modern elements in building design method is necessary to cultivate and strengthen the local value to be preserved in the modern era and to enrich the culture itself. In the case of this P-House study we can describe the existence of local and modern values in the building into the concept of tread, shape, space, structure, and material and then to find out the dominating aspect between local and modern values of the three building segments. The results of the process will demonstrate the dominance and placement of local and modern elements chosen by Budi Pradono in designing the P-House. The study used a descriptive method to describe the study object, analytic method to dissect the study object with theory, and interpretive method in drawing conclusions in an attempt to understand the dominance of local and modern values in the design method as well as to define the form of acculturation used or classified through the design of residential buildings. © 2020 Adityo Purnomo, Bachtiar Fauzy